The Subdiaphragmatic Angle of the Gastric Tube in Neonates - A Potential Predictor for Perforations? Kann der subdiaphragmatische Winkel von Magensonden in Rontgenaufnahmen von Neonaten als potentieller Pradiktor fur Perforationen genutzt werden? - Diez, Sonja; Bartos, Hilda; Siemes, Anna; Gerleve, Hubert; Schock, Alexandra; Besendörfer, Manuel; Mahnken, Andreas H.; Weiβ, Christel; Felderhoff-Müser, Ursula; Müller, Hanna (Klinische Pädiatrie, 2023)
Background Traumatic subdiaphramatic perforation of esophagus or stomach in neonates represents a rare clinical complication following the insertion of a gastric tube and is associated with high morbidity and mortality. The aim of the present study was to evaluate whether the angle of the gastric tube depicted on a plain radiograph may serve as a diagnostic tool to predict subdiaphragmatic traumatic (or iatrogenic) perforation. Patients and methods Thoraco-abdominal radiographs of 128 preterm and term neonates without perforation and 15 neonates with perforation of the esophagogastric junction or the stomach were retrospectively analysed. Results The angle of the gastric tube increases with postnatal age (p=0.0380). In the control group, the angle of the gastric tube varied between 13° and 48° (median: 31°), whereas the values ranged from -31° to 42° (median: 11°) in neonates with subdiaphragmatic perforation. Perforation should thus be suspected in cases with an angle of<20° (sensitivity: 93.3%; specificity: 91.4%). Moreover, an unusual localization of the tip beyond the gastric bubble is highly indicative of perforation. Discussion The present study emphasizes the importance of verifying the correct course of an inserted gastric tube. Conclusions In daily clinical practice, an angle of<20° should be followed by thorough physical examination, abdominal ultrasound and if applicable contrast medium examinations to exclude perforation.
CRIS-Team Scopus Importer:2024-12-16
Keywords: angle of gastric tube; neonatal gastric perforation; pneumoperitoneum; preterm neonates; thoraco-abdominal radiograph